Anonymous job applications in Europe - Annabelle Krause; Ulf Rinne; Klaus F. Zimmermann (IZA Journal of European Labor Studies, 2012)
Numerous empirical studies find a substantial extent of discrimination in hiring decisions. Anonymous job applications have gained attention and popularity to identify and combat this form of discrimination. To test whether their intended effects result in practice, in several European countries such as Sweden, France and the Netherlands field experiments were recently conducted. Also in Germany, a large field experiment has examined the practicability and potentials of this approach. Against the background of the recent German findings as novel evidence, this paper discusses the advantages and disadvantages of this new policy proposal.
Keywords: M51; J71; J78; 330; anonymous job applications; discrimination; hiring; Personalauswahl; Datenschutz; Arbeitsnachfrage; Arbeitsmarktdiskriminierung; Gleichberechtigung; Deutschland